Deep Learning Technologies in Enhancing Speaking Proficiency: A Literature-Based Analysis of a New Pedagogical Paradigm in TEFL - Rampeng Rampeng; A. Rizal; Dewi Nopitasari; Ulfah Syam (Lingua Franca, 2025)
This study explores how deep learning (DL) technologies, particularly those integrated into tools such as automatic speech recognition (ASR), text-to-speech (TTS), and AI-powered pronunciation applications, can transform speaking instruction by introducing a new pedagogical paradigm. Through a qualitative, literature-based methodology, this research analyzes thirty peer-reviewed studies published between 2020 and 2025. The findings reveal that DL tools significantly enhance learners’ pronunciation, rhythm, and fluency through real-time feedback and adaptive learning paths. In addition, these tools contribute to affective gains by reducing speaking anxiety and increasing learner motivation. However, challenges such as algorithmic bias, limited effectiveness in pragmatic discourse, and a lack of teacher training remain significant barriers to full integration. The discussion highlights the shifting role of TEFL instructors from content deliverers to facilitators of technology-enhanced learning environments. The study also emphasizes the importance of considering ethical implications and ensuring data privacy when implementing DL applications. Recommendations are provided for educators, institutions, and researchers to foster effective, equitable, and sustainable use of DL in language education. By bridging the gap between AI technologies and pedagogical practice, this paper proposes a forward-looking framework that positions deep learning not merely as a tool but as a transformative force in TEFL speaking instruction.